Prognostic value of normal sodium levels in patients with metastatic renal cell carcinoma receiving tyrosine kinase inhibitors - Roviello, Giandomenico; Catalano, Martina; De Giorgi, Ugo; Maruzzo, Marco; Buti, Sebastiano; Gambale, Elisabetta; Procopio, Giuseppe; Ottanelli, Carlotta; Caliman, Enrico; Isella, Luca; Sepe, Pierangela; Brighi, Nicole; et al. (Frontiers in Oncology, 2022)
Background Although serum sodium concentration, particularly hyponatremia, has been shown to be a prognostic marker of survival in metastatic renal cell carcinoma (mRCC), the impact of normal sodium levels has not been investigated. Herein, we investigate the influence of normonatremia in mRCC patients treated with tyrosine kinase inhibitors (TKIs). Materials and methods For this retrospective study, the clinical and biochemical data of patients treated with first-line TKIs for mRCC were available from seven Italian cancer centers. We collected natremia levels at baseline and first evaluation after treatment excluding patients with sodium levels outside the normal range (<135 or >145 mEq/L). The remaining patients were subdivided into two groups according to the median sodium value: natremia patients with <140 mEq/L (n = 132) and baseline natremia patients with ≥140 mEq/L (n = 185). Subsequently, we analyzed the impact of sodium levels on response rate (RR), disease control rate (DCR), progression-free survival (PFS), and overall survival (OS). PFS and OS were estimated through the Kaplan–Meier method, and differences between groups were examined by the log-rank test. Univariate and multivariate Cox regression analyses were applied to evaluate the prognostic factors for PFS and OS. Results Of the 368 patients, 317 were included in the analysis, 73.1% were men, and the median age was 67 years (range 36–89). When comparing patients with baseline natremia ≥140 mEq/L (n = 185) to patients with natremia <140 mEq/L (n = 132), the PFS was 15 vs. 10 months (p < 0.01) and the OS was 63 vs. 36 months, respectively (p = 0.02). On the first evaluation, patients with serum sodium ≥140 mEq/L had longer PFS (15 vs. 10 months, p < 0.01) and OS (70 vs. 32 months, p < 0.01) than patients with levels <140 mEq/L. Moreover, clinical outcomes showed a significant improvement in patients with natremia ≥140 mEq/L compared with patients with levels <140 mEq/L both at baseline and first evaluation: PFS was 19 vs. 11 months (p < 0.01) and OS was 70 vs. 36 months (p < 0.01), respectively. Conclusions To the best of our knowledge, this is the first study to investigate the impact of normonatremia in mRCC. We found that serum sodium levels <140 mEq/L at baseline and first assessment are independently associated with worse PFS and OS in mRCC patients treated with TKIs in the first-line setting.